Equity issuance motives and insider trading - Rossi, Anna; Sahlström, Petri (Journal of Corporate Finance, 2019)
The paper examines whether insider trades that are made close to corporate equity issues contain information about the issue policies, specifically about the size of the proceeds collected and their subsequent use. We find that equity issuers characterized by more prevalent insider purchases tend both to raise less equity capital and to spend a larger portion of the cash proceeds immediately in comparison to issuers characterized instead by insider selling. Additional tests provide evidence that issuers exhibiting more insider buying spend immediately greater amounts of the issue proceeds on investments including capital expenditures and research and development. The findings are consistent with the view that issuers associated with more extensive insider buying tend to raise equity capital in response to funding needs, whereas issuers characterized more by insider selling do so for market timing purposes. Taken together, these results imply that top managers are consistent in their personal trading decisions and in the corporate policies they pursue.